MANAGEMENT OF FINANCIAL SUPPORT OF HEALTHCARE DEVELOPMENT - FILIPOVA, N. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article focuses on the system of financial support for the development of health care. The efficiency of the health care sector is determined by the choice of its financial support model. An important aspect of the effectiveness of the financial model is the division of responsibilities between its key players. The initial parameters of the choice of the model of financial support for the development of health care are the features of the historical development of the country, socio-economic development, features of domestic policy. The functions of management of financial support for the development of health care, which include general management functions and functional impact on the objects of management. The principles of management of financial support for the development of health care - subsidiarity, social justice, cost-benefit, the principle of systematization, the principle of balance, the principle of diversification of financial support, responsibility, transparency, efficiency. The structure of health care development management, its levels and management technologies are considered. It is established that the management of financial support for the development of health care is under the influence of state and market regulation. The main tools for the formation of financial resources - government, insurance, tax, financial forecasting - are also identified. The key organizational role in the management of financial support for the innovative development of health care is assigned to public authorities, local governments and other bodies involved in the implementation of health policy.
Keywords: financial support; management; health care